Similarity Analysis of Understorey Plant Species in Forest Areas - Ternala Alexander Barus; Budi Utomo; Delvian; Fathiatul Rizkia Aulin; Sidabukke , Simon (Talenta Publisher, 2022)
Many forests have substantial understorey plants. These plants have an important contribution to soil and water conservation. The similarity index determines the resemblance of species structure and composition in a community. This research is aimed to see the impact and relationship of changes in the allocation of forest areas to the similarity of understorey species. The research was conducted using the line plot sampling method, sized 2 m x 2 m, with the understorey plants observed have been measured from germination to young plant (height 1.5 m). The number of plots in the plantation forest is 480 plots, protected areas 224 plots, and natural forest 96 plots. Determination of the number of understorey plots based on the minimum representative area curve. A Similarity Index was performed to analyze the data.Â The results indicated that there is an impact of changes in the forest area on the similarity of understorey species. It is known from the low similarity index value at the research location. It is due to the differences in environmental factors at the two locations such as air humidity, air temperature, the intensity of sunlight, and different patterns of forest area management.